Tertiary survey in polytrauma patients should be an ongoing process. Issue 4 (April 2016) - Ferree, Steven; Houwert, Roderick M.; van Laarhoven, Jacqueline J.E.M; Smeeing, Diederik P.J.; Leenen, Luke P.H.; Hietbrink, Falco
Abstract: Introduction: Due to prioritisation in the initial trauma care, non-life threatening injuries can be overlooked or temporally neglected. Polytrauma patients in particular might be at risk for delayed diagnosed injuries (DDI). Studies that solely focus on DDI in polytrauma patients are not available. Therefore the aim of this study was to analyze DDI and determine risk factors associated with DDI in polytrauma patients. Methods: In this single centre retrospective cohort study, patients were considered polytrauma when the Injury Severity Score was ≥16 as a result of injury in at least 2 body regions. Adult polytrauma patients admitted from 2007 until 2012 were identified. Hospital charts were reviewed to identify DDI. Results: 1416 polytrauma patients were analyzed of which 12% had DDI. Most DDI were found during initial hospital admission after tertiary survey (63%). Extremities were the most affected regions for all types of DDI (78%) with the highest intervention rate (35%). Most prevalent DDI were fractures of the hand (54%) and foot (38%). In 2% of all patients a DDI was found after discharge, consisting mainly of injuries other than a fracture. High energy trauma mechanism (OR 1.8, 95% CI 1.2–2.7), abdominal injury (OR 1.5, 95% CI 1.1–2.1) and extremity injuries found during initial assessment (OR 2.3, 95% CI 1.6–3.3) were independent risk factors for DDI. Conclusion: In polytrauma patients, most DDI were found during hospital admission but after tertiary survey. This demonstrates that the tertiary survey should be an ongoing process and thus repeated daily in polytrauma patients. Most frequent DDI were extremity injuries, especially injuries of the hand and foot.